Impact of Employee Value Proposition on Hotel’s Employee - Tiurida Lily Anita; Elang Kusumo; Sarfilianty Anggiani (University of Merdeka Malang, 2021)
This study aims to determine the direct and indirect influence between employee value proposition (EVP), and employee satisfaction (ES) on employee productivity (EP) in the Hospitality Industry, during the Covid 19 pandemic. This research was conducted by conducting observations and surveys to several hotels around the Jakarta area. Respondents in this study were employees who worked at the Hotel as many as 133 respondents, with sampling techniques using purposive sampling, data collection was conducted with the dissemination of questionnaires and this research was conducted with a descriptive quantitative approach. The analysis technique used is path analysis. The results showed that EVP had a positive and significant direct and indirect effect on employee productivity.